Arithmetic expression | ||||||||||||
simple arithmetic expression, assignment | ||||||||||||
int f, g, h, i, j; | $s0 | (g + h) - (i + j) | ||||||||||
f = (g + h) - (i + j); | $s1 | i + j | ||||||||||
$s2 | h | |||||||||||
$s3 | i | |||||||||||
$s4 | j | |||||||||||
assume variables are assigned to $s0, $s1, $s2, $s3, $s4 respectively | ||||||||||||
add $s0, $s1, $s2 | # $s0 = g + h | |||||||||||
add $s1, $s3, $s4 | # $s1 = i + j | |||||||||||
sub $s0, $s0, $s1 | # f = (g + h) - (i + j) | |||||||||||